IMPLEMENTASI ELECTRONIC COSTUMER RELATIONSHIP MANAGEMENT (E-CRM) SEBAGAI SISTEM INFORMASI DALAM PENINGKATAN LAYANAN PESERTA DIDIK DI BIMBEL EXPRESS BERBASIS CRM TOUCHING APPLICATION - dian lesmana; Fahmi Yusuf; dede Irawan (Sistem Informasi Fakultas Ilmu Komputer Universitas Kuningan, 2019)
Non-formal education is an every opportunity where there is regular and directed communication outside of school, where a person gets information, knowledge, training or guidance according to his age and life needs with the aim for developing the level of skills, attitudes of participant that is efficient and effective in the family and even the community and country. In Indonesia, education is placed as a must for every Indonesian citizen. However, the current non-formal education is less popular. It can be identified with the number of existing unemployment, this will have a bad impact if it is left unchecked (